MEKANISME PATOFISIOLOGIS DAN TATA LAKSANA KLINIS PUBERTAS PREKOKS: SEBUAH TINJAUAN TERINTEGRASI - Melya Susanti (Yayasan Nusantara Hasana Berdikari, 2025)
Precocious Puberty: Etiology, Psychosocial Impact, and Management Puberty is a complex biological process characterized by activation of the hypothalamic–pituitary–gonadal (HPG) axis, resulting in both physical and psychosocial changes. Precocious puberty (PP) is defined as the onset of pubertal signs before the age of 8 years in girls and 9 years in boys. This condition is classified into central precocious puberty (CPP), caused by premature activation of the HPG axis, and peripheral precocious puberty (PPP), which occurs independently of gonadotropin stimulation. Globally, the prevalence of PP has been rising, particularly among girls, with epidemiological studies from Denmark to various Asian countries reporting similar trends. Contributing factors include genetic variations (such as mutations in MKRN3 and DLK1), dysregulation of KNDy neurons, epigenetic mechanisms, obesity, nutritional patterns, exposure to endocrine-disrupting chemicals, and psychosocial stress. The consequences of PP extend beyond accelerated growth and compromised adult height prediction, encompassing psychosocial dimensions such as heightened anxiety, reduced selfesteem, social stigma, and difficulties in academic performance and peer relationships. Early diagnosis and appropriate management—particularly the use of gonadotropin-releasing hormone (GnRH) agonists in CPP—have proven effective in delaying pubertal progression and mitigating long-term sequelae. Given the increasing prevalence, a comprehensive understanding of the etiology, clinical consequences, and management strategies for PP is essential for both clinicians and researchers.